Gendarmerie Railway Police of Russian Empire in Early 20th Century: Working with Political Agents - R. A. Arslanov; P. A. Kolpakov (Научный диалог, 2023)
The study examines the historical experience of interaction between the gendarmerie railway police of the Russian Empire and covert informants in political organizations. It explores the establishment of intelligence work on railways, the monitoring of its effectiveness, the verification of the reliability of secret agents, and the identification of provocateurs and blackmailers among them. The materials for analysis are extracted from previously unpublished secret and top-secret case files of the gendarmerie police departments of the railways. The authors provide their own definition of intelligence work. It is emphasized that priority was given to recruiting informants who had a financial interest in collaborating with the police. The study demonstrates that the value of information obtained by secret agents was the main criterion for evaluating the effectiveness of financial resources allocated to intelligence work. The authors highlight the need for caution in establishing relationships between railway gendarmes and informants due to the possibility of assassination attempts against handlers or the provision of misinformation. The study concludes that assigning the duty of recruiting political agents and obtaining information through them was justified by the need to suppress revolutionary movements, but inertia in acquiring informants and the scale of crises in the empire prevented the achievement of the set goal.